(untitled) (Communications in Mathematical Research, 2021)
In this paper, empirical Bayes test for a parameter θ of two-parameter exponential distribution is investigated with replicated past data. Under some conditions, the asymptotically optimal property is obtained. It is indicated that the rate of convergence can be very close to O(N^−12 ) in this case that a parameter µ is known.